Modern Wicca: a history from Gerald Gardner to the present - Howard, Michael (Llewellyn Publ., 2009)
Journeying to foreign lands -- Into the witch cult -- The Pickingill connection -- Gerald Gardner and the great beast -- A magical book of shadows -- The Museum of Witchcraft -- Witchcraft today -- Enemies within and without -- New witch blood -- Pretenders and rivals -- The king of the witches -- The politics of Wicca -- The Pagan Federation emerges -- Wicca international -- Witches in cyberspace -- Wiccans in the 21st century